KOMBINASI METODE PARTIAL LEAST SQUARE (PLS) DAN TECHNOLOGY ACCEPTANCE MODEL (TAM) : EVALUASI PEMBELAJARAN (PRAKTIKUM ONLINE) - Nariza Wanti Wulan Sari; Ika Purnamasari; Fahrullah Fahrullah (LP3M Universitas Mulia, 2020)
Corona virus disease (Covid-19) pandemic give effect in education. During the pandemic, the learning process was done online both of theory and practicum based on the e-learning system. Combination of partial least square (PLS) method and technology acceptance model (TAM) method used to evaluate the learning process to know students’ understanding especially practicum online. Variables using in TAM are perceived ease of use, perceived usefulness, attitude toward using, and behavioral intention. The results of this research show that there is a positive attitude by students who feel easy to do the online practicum. However, this not affects their enthusiasm to do online practicum again.